Good Village Governance in Financial Management to Create Independent Village: Study of Pecatu Village Government - Bayu Adhinata; I Ketut Darma; Ni Wayan Sirimiati (Soshum: Jurnal Sosial dan Humaniora, 2020)
Village independence is a central issue that is of concern to the government at this time. Village funds provided by the central and regional governments are a way to realize development starting at the village level. The assumption is that when the village is economically, socially, and politically independent, it will support the strength of the state. However, village funds must also be appropriately managed so that village development can be maximized. Good management is an absolute focus to make it happen. Pecatu Village as one of the villages that receive village funds must also make good arrangements to create an independent Pecatu Village, one of which is through village financial management towards an independent village. This study aims to see how the implementation of good village governance through good village financial management is to create an independent village. This study uses a qualitative approach to seeing and analyzing the phenomena and events that occur in the village of Pecatu. The informants in this study were the Head of Pecatu Village, the Head of Government Affairs, the Head of Financial Affairs, and the people of Pecatu Village. The results of this study indicate that Pecatu Village has implemented the principles of good village governance in village financial management to create village independence. One of the efforts to create an independent village is through optimizing the role of village-owned enterprises that help improve the community's economy and village income.